Ảnh hưởng của rủi ro địa chính trị đến rủi ro phá sản của ngân hàng thương mại - Nguyễn Thành, Công; Ngô Hồng, Hạnh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
Using a panel of 431 commercial banks in the United States over the period 2006–2021, this paper examines the impact of geopolitical risk on bank risk-taking. Our regression results indicate that geopolitical risk increases bank default risk. Delving into the components of geopolitical risk, the authors find that the negative effects of geopolitical acts on bank risk-taking are more pronounced than those of geopolitical threats. Besides, the authors find that reducing bank profitability and increasing earnings volatility are two channels through which geopolitical risk increases bank risk-taking.